The Effectiveness of Using Hand Puppet Video towards Student's Listening Comprehension in Narrative Text - Ayu Safaroh; Yudi Juniardi; Ika Handayani (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2022)
The objective of this research was to find out the significant effect of using Hand-Puppet Video towardstudents’ listening comprehension in learning narrative text. This research used quantitative methodand quasi experimental design. This research was conducted at eighth gradeof SMPN 1 PONTANG inacademic year 2021/2022. The experimental class was taught by using hand-puppet media and the controlclass without using hand-puppet media. The samples of this research were VIII A as experimentaldesign and VIII B as control class, each class consisted 30students. The data was collected by usingtest which consisted of pre-test and post-test. The calculating from t-test showed that the value of t-testwas higher than the value of t-table (7.177 ≥2.00) at the level of significant of a 0.05 and degree of freedomis 58. It means that the alternative hypothesis was accepted and null hypothesis was rejected and theresult of the research showed that using hand-puppet media had significant effect towards students’listening comprehension. From those findings, it could be concluded that there was significant effectof using hand-puppetmedia towards students’ listening comprehension in narrative text learning ateighth grade of SMPN 1 PONTANG.